Mechanical reinforcement of copper films with ceramic nanoparticles - Leifert, Annika; Mohamed-Noriega, Nasser; Meier, Andreas; Mondin, Giovanni; Dörfler, Susanne; Grothe, Julia; Kaskel, Stefan; Schumm, Benjamin; Nowka, Christian; Hampel, Silke; Cuéllar, E. López (Ceramic Engineering and Science Proceedings, 2014)
Metal matrix nanocomposites are promising materials for applications in aerospace, automotive and electronic industries due to their excellent mechanical and physical properties. Here, a new synthesis route is developed for the preparation of ceramic particulate reinforced metal films. The homogeneous distribution of different ceramic nanoparticles (TiO2, TiC and SiC) in the range of 5-10 wt.% into copper films by a wet chemical approach results in metal matrix composites with metallic electrical conductivity and enhanced hardness and wear resistance. Reinforcing material and concentration thereof can be easily varied owing to the polymer precursor memod that is established. Electrical conductivity is marginally impaired compared to pure copper films, but still in the range of metallic conductivity. Hardness is analyzed by nanoindentation of the films. Highest hardness is found for 10 wt.% TiO2 in copper (Hit = 1-39 GPa). Improved wear and scratch resistance are shown by a pencil hardness scratch test (Wolff-Wilborn, ISO 15 184).
CRIS-Team Scopus Importer:2023-03-20